Gagasan Penguasa Muslim dalam Pengembangan Budaya EKonomi (Umar Ibn Khattab, Umar Ibn Abdul Azis, Ghazan Khan, dan Al’uddin Khalji) - Troitje Patricia Aprilia Sapakoly (Universitas Islam Negeri Fatmawati Sukarno, 2020)
AbstractBeing a leader with the mandate to build a well-being community, surely, needs a strong commitment. Some aspects can be the indicators to measure the success of the leadership. One of the indicator is weather the leadership bringing the goodness for the society or not. In the history of Islam, there are some leaders that should be remember for their policies are still contribute for the economy development today. Umar Ibn Khattab, Umar Ibn Abdul Azis, Ghazan Khan and Al'uddin Khalji are the leaders whose ideas and economy policies can be used as the foundation to overcome the situation and condition of society. Their thoughts are influenced by the doctrine of Islam even their lifestyle is the better one to cope the economy problems in that day.This paper will discuss about 4 (four) figures with their backgrounds and policies which brought Islam to their glorious period. Their idea of economy as the moslem ruler at that moment is the contribution for the economic life of Islam, espescially how the leader doing their duties based on the Islamic values.Keywords : Islamic economy, Umar Ibn Khattab, Umar Ibn Abdul Azis, Ghazan Khan, Al’uddin Khalji, History.AbstrakMenjalankan mandat dan amanah sebagai pemimpin untuk menyejahterakan umat/masyarakat yang dipimpin membutuhkan komitmen yang kuat. Keberhasilan seorang pemimpin dapat dilihat dari berbagai segi. Salah satu keberhasilannya adalah ketika kepemimpinannya mendatangkan kemaslahatan bukan hanya bagi dirinya sendiri melainkan semua orang. Dalam catatan sejarah ke-Islaman, ada para pemimpin Islam yang patut diingat karena kebijakan-kebijakan mereka turut memberikan sumbangsih yang sangat besar atas perkembangan ekonomi yang ada pada saat ini. Umar Ibn Khattab, Umar Ibn Abdul Azis, Ghazan Khan dan Al’uddin Khalji merupakan para pemimpin yang gagasan dan kebijakan ekonominya dapat dijadikan landasan pemikiran untuk mengatasi situasi dan kondisi masyarakat. Pemikiran-pemikiran intelektual mereka dipengaruhi dengan ajaran Islam bahkan gaya hidup cukup terbukti dapat mengatasi persoalan ekonomi yang tidak baik pada masanya. Tulisan ini akan membahas keempat tokoh tersebut mulai dari latar belakang tokoh hingga kebijakan-kebijakan ekonomi yang membawa Islam pada masa kejayaan. Gagasan ekonomi mereka sebagai penguasa muslim pada saat itu merupakan kontribusi bagi kehidupan perekonomian Islam lebih-lebih pada bagaimana seharusnya pemimpin menjalankan tugas tanggung jawabnya berdasarkan nilai-nilai Islami.Kata Kunci : Ekonomi Islam, Umar Ibn Khattab, Umar Ibn Abdul Azis, Ghazan Khan, Al’uddin Khalji, Sejarah.